Nineteenth century narratives of contagion our feverish contact - Christensen, Allan Conrad 1940- (London New York Routledge, 2005)
This intriguing book examines the ways 'contagion' or disease inform and shape a wide variety of nineteenth century texts and contexts
Half Title: Nineteenth-Century Narratives of Contagion; TItle Page; Copyright; Dedication; Contents; Acknowledgements; Note on citations; 1 History as contagion; 2 Providence amidst pestilence and fire; 3 Swordsmen and needlewomen; 4 Physicians, nurses and patients; 5 Mothers, daughters and lovers; 6 Writers and readers; 7 Speakers, singers and listeners; Conclusion; Notes; Bibliography; Index
Includes bibliographical references (pages 293-342) and index. - Print version record
Keywords: English fiction -- History and criticism -- 19th century; Literature and medicine -- History -- 19th century -- Great Britain; Literature and medicine -- History -- 19th century -- Europe; Medicine in Literature; Literature and medicine -- Great Britain -- History -- 19th century; Literature and medicine -- Europe -- History -- 19th century; Communicable diseases in literature; Epidemics in literature; Diseases in literature; English fiction -- 19th century -- History and criticism; England -- Europe -- Great Britain; Communicable Diseases -- England; Disease Outbreaks -- England; History, 19th Century -- England; Medicine in Literature -- England; LITERARY CRITICISM ; European ; English, Irish, Scottish, Welsh; English fiction; Literature and medicine; Criticism, interpretation, etc; History; England; Europe; Great Britain; Electronic books -- Criticism, interpretation, etc -- History; Bibliografie